Association of MMP-7-181A>G Gene Polymorphism and Colorectal Cancer Risk at Prof.dr.I.G.N.G.Ngoerah General Hospital Bali - Chandra, Christian; Wihandani, Desak Made; Supadmanaba, I Gede Putu; Dewi, Ni Nyoman Ayu (E-Jurnal Medika Udayana; Vol 13 No 5 (2024): E-Jurnal Medika Udayana, 2024)
Background: Colorectal cancer is the third most diagnosed cancer worldwide and ranks second as the cause of cancer-related mortality. Matrix Metalloproteinase (MMP) enzymes are known to be closely associated with the carcinogenesis of colorectal cancer. The MMP-7-181A>G polymorphism has been previously linked to the risk of various types of cancer. However, the association of the MMP-7-181A>G polymorphism with the risk of colorectal cancer has not been investigated in Indonesia. Objective: This study aims to determine the relationship between the MMP-7-181A>G polymorphism and the risk of colorectal cancer. Methods: Polymerase chain reaction (PCR) followed by Sanger sequencing was employed to obtain genotype data from 26 cases and 26 controls. Univariate and bivariate statistical analyses were conducted to determine the association of MMP-7-181A>G polymorphism to the risk of colorectal cancer by evaluating obtained Odds Ratio (OR) and p-values. Results: The distribution of the AG and GG variants in the case group was 23.1% and 3.8%, respectively. Meanwhile, the distribution of the AG and GG variants in the control group was 15.4% and 0%. Data analysis shows an insignificant increase in colorectal cancer risk in genotypes with the G allele (OR=2.02, 95% CI: 0.51-8.00, p=0.308). Conclusion: The study suggests that the MMP-7-181A>G polymorphism cannot be directly associated with colorectal cancer risk, emphasizing the need to consider multiple interactions with other MMP gene polymorphisms. Further investigations into direct associations of this polymorphism with MMP-7 expression levels in colorectal cancer lesions could help give a clearer understanding of genetic risk factors in colorectal cancer.